De Ceylan à l’Écosse : le « Voyage dans les Lowlands » de Nicolas Bouvier, ou l’art de rapprocher les cultures - Liouba Bischoff (Viatica)
In the 1980s, Nicolas Bouvier travelled not only to the East, where he had discovered cultures thousands of years old, but also to Ireland and Scotland. The “Voyage dans les Lowlands”, less well known than the Journal d’Aran, mischievously inverts the relationship between the age of the traveller and the age of the countries he visited: after visiting "the old", Bouvier turns to "the young" to regain a little freshness, but he does not see these experiences as separate. Spatial decentring takes the form of an intimate refocusing: Bouvier orientalises Scotland, a country about which he knows almost nothing at the outset, but which gradually joins his vision of history and the mosaic of cultures, where all connections are good for recreating the harmonic sphere of creation.